Saproxylic beetles in two types of fine woody debris of Norway spruce - Manak, Vitezslav (SLU/Dept. of Ecology, 2007)
Fine Woody Debris (FWD) has been considered as the promising source of forest fuel in Fennoscandia. Main sources are logging residues which formerly were retained on clearcuts. Recent studies indicate that many saproxylic (wood-living) organisms use this wood, and the harvest may decrease their breeding substrate. However, dead branches of thin diameters constitute a common substrate in closed canopy forest stand. If the fauna of dead branches is similar to that of clearcuts, the negative effects of forest fuel harvesting should be considered rather small. The aim of this study was to compare saproxylic beetle fauna between (1) spruce twigs retained on one-year-old clearcuts and (2) dying bottom branches attached to living trees. I examined the effect of twig type, twig diameter, sun exposure and height on densities of species and individuals as well as on species composition of saproxylic beetles. Twig type was the most explanatory variable and higher densities of species and individuals were found in retained twigs on clearcuts. There were species specifically associated with retained twigs as well as with dying bottom branches. In addition to twig type there was a significant effect of height and sun exposure as those beetles being abundant in dying bottom branches were more common either in open conditions or in branches high above the ground. The results indicate that FWD is not a homogenous substrate for saproxylic beetles. If the pattern is similar for other tree species, the forest fuel harvesting may have negative effect on saproxylic beetles utilizing the dead wood of fine diameters.